Psikoanalisis Tokoh Remaja dalam Novel Misteri Cinta Segi Lima karya S.Mara GD - ROKHMAWAN, TRISTAN; FITRIYAH, LAILATUL (Hasta Wiyata, 2019)
Teenagers figure in MCSL novels have psychological problems due to family chaos and divorce, they behave deviantly. This paper discusses the psychology of adolescent figures in the MCSL by applying Freud's psychoanalytic theories. Psychoanalytic theory is used to find out how deviations occur in characters and what causes them. The difference seen is in the way they react to the id and anxiety’s pressure. Not all teens react negatively or aggressively to the problems they face. Parenting style and closeness between family members determines the output of behavior that is raised by adolescents as a reaction to the problems they face. Adolescents with good parenting and closeness, to the parents, can refrain them from aggressiveness actions. S. Mara GD., as a novel writer, proved to be very capable of developing the personality of adolescents figures in his novel in real terms. The aesthetic and mimetic intelligence in the MCSL novel is shown by presenting teen figures who are psychologically real.